Antenna array signal processing based methods for target detection and source estimation - Huang, Ling (2014)
Antenna arrays provide significant contributions in areas such as wireless communications, radar and sonar. Antenna array signal processing has been gaining great interests in two major types of applications, target detection and source estimation. Target detection is important in areas such as fire rescuing, anti-terrorist and surveillance, in which through-the-wall (TTW) target detection and line-of-sight (LOS) target detection are equally demanded. Source estimation is important in areas such as vehicle tracking, patient safety, medical instrumentation monitoring and direction finding.